Mediation of land disputes between PT Perkebunan Nusantara (PTPN) VII Cinta Manis and Rengas Village Farmers, Ogan Ilir Regency Sumatera Selatan Province - Octaleny, Ellyza; Larasati, Endang; Suwitri, Sri; Kismartini, Kismartini (Management and Entrepreneurship: Trends of Development, 2020)
Dispute resolution is indeed difficult to do, but that does not mean that it is impossible to materialize. The main capital of settlement through mediation is the willingness and good faith of the disputing parties to end the dispute that occurs between the two disputing parties. The purpose of this study was to analyze the mediation of land disputes between PT Perkebunan Nusantara (PTPN) VII Cinta Manis and Rengas Village Farmers, Ogan Ilir Regency, Sumatera Selatan Province. The research method used in this research is descriptive qualitative method. Data collection techniques are by means of interviews, observation and documentation. The findings in this study are that there is no neutrality of the mediator in resolving land disputes so that the mediation fails to reconcile the two parties to the dispute. The factors that determine the success of the mediation process are volunteerism to carry out mediation, confidentiality, and neutrality of the mediator. The conclusion in this study is that mediation will work well if the parties voluntarily agree to mediate and the mediator can be neutral in resolving land disputes. JEL Classification: D74, Q24